Mechanical circulatory support as a cornerstone in advanced heart failure and transplantation - Braga, Marta; Pinho, Ana Isabel; Jorde, Ulrich; González-Costello, José (Frontiers in Cardiovascular Medicine, 2025)
Orthotopic heart transplantation remains the gold standard for managing selected patients with end-stage heart failure (HF) who are unresponsive to conventional therapies. Mechanical circulatory support (MCS), encompassing durable (dMCS) and temporary (tMCS) devices, has become a cornerstone in bridging patients to transplant (BTT) and also addressing the increasing burden of advanced HF with dMCS destination therapy. Each type of MCS offers distinct advantages tailored to specific patient needs and clinical scenarios. This review summarizes the features of MCS devices, their implications in clinical practice, and their impact on patient outcomes. Evidence demonstrates that dMCS, including the widely used durable left ventricular assist device HeartMate 3, significantly improves the prognosis of waitlisted patients and is associated with better post-transplant outcomes compared to tMCS when used as a BTT strategy. However, recent trends in allocation systems favor prioritizing tMCS-supported patients to improve outcomes for sicker individuals, underscoring the complexity of resource allocation. In this context, recent tMCs devices such as the Impella 5.5 have demonstrated promising early results as BTT, and ongoing larger studies with long-term follow-up will be crucial to better define their optimal indications and patient selection. Additional research is required to ascertain whether urgency-based models provide the most equitable distribution of resources while optimizing both pre- and post-transplant outcomes. Continued innovation in MCS technology, alongside the development of personalized treatment strategies, is vital to address the evolving needs of the growing advanced HF population. Future advancements should prioritize creating devices that are easier to implant, feature wireless power sources, and provide more physiological support, ultimately enhancing the care and outcomes of patients with advanced HF.